What is the role of combination drug therapy in the treatment of overactive bladder? ICI‐RS 2014. Issue 2 (February 2016) - Visco, Anthony G.; Fraser, Matthew O.; Newgreen, Donald; Oelke, Matthias; Cardozo, Linda
Abstract : Aims and Methods: The role of combination therapy using oral antimuscarinic medications for the treatment of overactive bladder was proposed at the 2014 International Consultation on Incontinence‐Research Society in Bristol, UK to identify key factors to consider when making clinical decisions and to guide future research design. Results: Combination therapy is justified if monotherapy is associated with suboptimal efficacy or bothersome side effects. Combination therapy has the potential to improve efficacy with fewer side effects than monotherapy. Two Phase 2 studies comparing combination therapy that included an antimuscarinic demonstrated improvement in mean voided volume, the primary outcome chosen, with some combinations showing improved micturition frequency and quality of life. The two studies found no evidence of an increased safety risk with combination therapy compared to monotherapy. Future studies should use clinically meaningful or patient reported outcomes such as incontinence episodes when comparing efficacy. If surrogate measures are used, a clear justification should be provided. Cost analyses should be planned for clinical research trials evaluating combination drug therapy. Conclusions: Combination therapy is reasonable when monotherapy has suboptimal efficacy or bothersome side effects. Future research studies evaluating combination therapy for urgency urinary incontinence should ideally 1 be performed as part of a randomized clinical trial, 2 evaluate non‐responders to monotherapy, 3 evaluate combination therapy using medications with different mechanisms of action, 4 include clinically meaningful and patient reported outcomes when evaluating efficacy, and 5 include cost‐effectiveness analyses to justify any increased cost by showing improvement in efficacy or reduction in side effects. Neurourol. Urodynam. 35:288–292, 2016 . © 2016 Wiley Periodicals, Inc.